A core SMRT corepressor complex containing HDAC3 and TBL1, a WD40-repeat protein linked to deafness - Guenther, Matthew G. (Cold Spring Harbor Laboratory Press, 2000)
The corepressor SMRT mediates repression by thyroid hormone receptor (TR) as well as other nuclear hormone receptors and transcription factors. Here we report the isolation of a novel SMRT-containing complex from HeLa cells. This complex contains transducin β-like protein 1 (TBL1), whose gene is mutated in human sensorineural deafness. It also contains HDAC3, a histone deacetylase not previously thought to interact with SMRT. TBL1 displays structural and functional similarities to Tup1 and Groucho corepressors, sharing their ability to interact with histone H3. In vivo, TBL1 is bridged to HDAC3 through SMRT and can potentiate repression by TR. Intriguingly, loss-of-function TRβ mutations cause deafness in mice and humans. These results define a new TR corepressor complex with a physical link to histone structure and a potential biological link to deafness.